The influence of saturation and loading angle on sandstone damage characteristics after freeze-thaw cycle - Shihao Yuan; Jiaxu Jin; Xiaoli Liu; Shaohua Li; Bing Liang (Geomatics, Natural Hazards & Risk, 2023)
AbstractThe strength deterioration and fracture tendency of freeze-thaw rock determine the construction and operation safety of rock engineering. This article conducted compression-shear composite load tests on sandstones with various saturations to examine the failure law of rocks in cold climates and the contributing elements of strength degradation. It was found that with an increase in saturation and loading angle, the compressive strength and elastic modulus dropped. The concept of freeze crack threshold and saturation threshold was proposed. The peak shear stress was negatively correlated with saturation and positively correlated with loading angle. The σCI (crack initiation stress) and σCD (crack damage stress) in the saturated state were only 39.91% and 45.18% of those in the dry state. Serious damage occurred at high saturations, which is consistent with the scanning electron microscopy results. The σCI and σCD under 30°loading angle are 49.72% and 42.91% of those under uniaxial, respectively. This is mainly due to the change of the failure mode from tensile-shear failure to combined tension-shear failure, and finally to single-shear failure. A strength prediction model was established based on sandstone damage characteristics. The research results have important reference value for rock engineering design in frigid climates and complex load environments.